PENGARUH PENGALAMAN, ORIENTASI ETIKA, KOMITMEN DAN GENDER TERHADAP SENSITIVITAS ETIKA AUDITOR (Studi Empiris Pada Inspektorat Provinsi Jawa Tengah) - Anisah, 14.05.52.0201; Badjuri, Achmad (Students' Journal of Accounting and Banking, 2018)
The purpose of this research to test and analyze the influence of experience,ethical oriented, commitment and gender to auditor ethics sensitivity at the Inspectorate of Local Goverment in Central Java. The population in this research is auditor and all apparatus of Inspectorate of Central Java Provincial Goverment involved in examination task with having experience working minimum 2 years, sampling was conducted using a purposive sampling method and number of samples 40 respondents. The data were obtained from the primary source, collected by using survey methid by distributing questionnaire directly. The data analyziz techniue used in this research is the technique of multiple regression analysis. The results showed that professional commitment had a significant positive effect on auditor ethics sensitivity. While experience, idealism, organizational and gender commitment have no significant positive effect on auditor ethics sensitivity. Relativism has no significant negative effect on the auditor's ethical sensitivity.Keywords : experience, idealism, relativism, profesional commitment, organizational commitment, gender and auditor ethics sensitivity